HUBUNGAN KESEHATAN RUMAH TINGGAL TERHADAP KEJADIAN PNEUMONIA BALITA DI DESA SAMBANGAN KECAMATAN BATI-BATI KABUPATEN TANAH LAUT TAHUN 2012 - Sari, Nata Lisa Ervina; Marlinae, Lenie; Noor, Frieda Anie (Universitas Lambung Mangkurat, 2014)
Pneumonia is an infectious disease that requires special attention, because it is included in the leading cause of pneumonia morbidity and mortality in children under five years old, especially in Indonesia. Construction of homes and neighborhoods that do not meet the health requirement is a risk factor in the transmission of various types of disease-based environment, one of pneumonia. This study aimed to determine the relationship of home health care live on the incidence of pneumonia in children under five in the village of Bati-Bati district Sambangan Tanah Laut Â in 2012. This study was observational analytic cross-sectional approach to sampling purposive sampling. Found a total of 36 respondents consisted of 12 respondents with pneumonia and 24 respondents not pneumonia. Fisher Exact test analysis at 95% confidence level. The results showed that there is a relationship between ventilation (p = 0.029), ceiling (p = 0.011), window (p = 0.020), the division of space (p = 0.011) and residential density (p = 0.007) with the incidence of pneumonia. This matterÂ was supported with result of observation showing house construction some part of ineligibility. While roof (p = 0.727), walls (p = 0.536), and floor (p = 0.278) there was no association with the incidence of pneumonia.Â Keywords: pneumonia, home construction, children under five years old